VIDEO GAMES ARE AN INTERESTING OBJECT TO THE COGNITION STUDIES - Cleci Maraschin; Carlos Baum (Editora da Universidade de Santa Cruz do Sul, 2013)
Video games create a virtual space that can be inhabited in various ways by the players. Despite the controversies in which they are constantly included, electronic games bear witness to the modus operandi in our contemporary cognition permeated by technical objects. By focusing the know-how instead of a declarative experience the games open questions in the field of new literacies and problematize the use of technology in teaching practices. From the development of a locative game at the Botanical Garden of Porto Alegre, this article discussed some, methodological, political and theoretical implications arising from the research with video games in the field of cognitive studies. We discuss, finally, three theoretical / methodological implications the practice with video games forces us to think: research the video game through the process of its operation, questioning cognitive policies that organize our everyday and map the complex web of practices that supports the use of technical objects.